A NOVEL ETIOLOGIC CONCEPT OF THE DISEASE. HERPESVIRUS - BACTERIA PATHOGENIC INTERACTION IN JUVENILE (AGGRESSIVE) PERIODONTITIS. REVIEW - Alexandru Flondor; Maria-Alexandra Martu; Irina-Georgeta Sufaru; George-Alexandru Maftei; Liliana Pasarin; Cristina Popa; Silvia Martu; Vasilica Toma (Romanian Dental Association for Education, 2023)
This article focuses on herpesviruses and major periodontopathic bacteria in the etiology of localized juvenile periodontitis. The joint association of herpesvirus with severe periodontitis and systemic diseases argues for a possible systemic involvement of periodontal herpesviruses in medical disorders and for periodontal therapy that targets both herpesviruses and bacterial pathogens. The etiopathogenesis of severe periodontitis includes active herpesviruses, specific bacterial pathogens, and pro-inflammatory cytokines. The inflamed periodontium constitutes an important reservoir of herpesviruses outside of the hematopoietic compartment. Several rationales prompted studies on periodontal herpesviruses. Severe periodontitis lesions can contain hundreds of millions of active herpesviruses and bacterial pathogens that may. Systemic and topical anti-herpesvirus therapy can neutralize active herpesviruses, and effective patient self-care can help prevent inflammatory cells containing latent herpesviruses from entering the periodontium.